2014
DOI: 10.1111/cea.12296
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial barrier function regulates the pathogenesis of allergic asthma

Abstract: The integrity of the airway epithelium in patients with asthma is often disrupted, with loss of epithelial cell-cell contacts. Airway epithelial barrier dysfunction may have important implications for asthma, because structural epithelial barrier function is tightly interwoven with the ability of the epithelium to regulate the immune system. We propose that changes at the airway epithelial barrier play a central role in the sensitisation to allergens and pathogenesis of allergic asthma. Many of the recently id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 139 publications
(158 reference statements)
2
88
0
Order By: Relevance
“…The epithelial protective mechanism is crucial, with recent studies indeed challenging the existing inflammation-dominant theory of asthma pathogenesis [26,27]. Evidently, most of the available genome-wide scan studies have indicated the possibility of the governing role of the airway epithelia in determining asthmatic airway inflammation [28]. In this context, we also found no alteration of goblet cell metaplasia with PBPB treatment (fig.…”
Section: Discussionsupporting
confidence: 53%
“…The epithelial protective mechanism is crucial, with recent studies indeed challenging the existing inflammation-dominant theory of asthma pathogenesis [26,27]. Evidently, most of the available genome-wide scan studies have indicated the possibility of the governing role of the airway epithelia in determining asthmatic airway inflammation [28]. In this context, we also found no alteration of goblet cell metaplasia with PBPB treatment (fig.…”
Section: Discussionsupporting
confidence: 53%
“…The bronchial epithelium is increasingly recognised as a critical airway cell involved in the pathogenesis and persistence of asthma [59]. This is highlighted by the altered function of the epithelium in patients with asthma compared with those without [60].…”
Section: Bronchial Epitheliummentioning
confidence: 99%
“…Reduced epithelial integrity or enhanced epithelial fragility has been put forward as a common cause for allergic disorders (Heijink et al, 2014), and increased release of these two cytokines upon epithelial challenge might be a hallmark of susceptibility to these diseases. This characteristic of allergic disease also identifies these two cytokines as key targets for future intervention.…”
Section: Genetic and Clinical Evidence For The Role Of Il-33 And Tslpmentioning
confidence: 99%